Syarat Subjektif Sahnya Perjanjian Menurut Kitab Undang-Undang Hukum Perdata (KUH PERDATA) Dikaitkan Dengan Perjanjian E-Commerce - Bayu Sugara; Moh Taufik Hidayat (JOURNAL SAINS STUDENT RESEARCH, 2023)
When we are dealing with e-commerce agreements, we have to remember that this kind of agreement is unknown in Indonesian Civil Code. The possible thing that might cross through our mind is the legal subjective requirements for this kind of agreement based on the Indonesian Civil Code in its relation to e-commerce agreement. These agreements are emerging as a result of information and technology development. Any people can enter into a business agreement through electronic communication media without face-to-face interactions. The aims of this writing are to identify the process of agreements in e-commerce transactions and to be able to identify the relation between the legal subjective requirements and e-commerce agreements entered by minor legal subject. The normative legal research is applied in this writing by using secondary data and legislation approach. There is “offer and acceptance” process in e-commerce 2 agreements found in this research and in term of e-commerce agreement abrogation, only parents or guardians could ask for abrogation to the judge if minor legal subject is willing to cancel the agreement. In other word, an e-commerce agreement will remain valid for both sides if there is no abrogation submitted by parents or guardians.